2018
DOI: 10.1097/ijg.0000000000000963
|View full text |Cite
|
Sign up to set email alerts
|

Near and Distance Stereoacuity in Patients With Primary Open-angle Glaucoma

Abstract: Near and distance stereoacuity were significantly lower among patients with POAG than among control subjects. Near stereoacuity worsened with increasing POAG severity but distance stereoacuity did not. However, the proportion of patients with a lack of distance stereoacuity was higher in the POAG group than in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, patients included in this study were specifically selected to have very early-stage glaucoma, no significant asymmetry in clinical measures between their right and left eyes, and the median stereopsis was within the normal population range. It has been previously shown that stereoacuity does deteriorate in early stages of glaucoma and it is more pronounced with severe disease 40,41. Whether patients maintain their binocular summation ability in moderate or late stage disease remains to be explored in future studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, patients included in this study were specifically selected to have very early-stage glaucoma, no significant asymmetry in clinical measures between their right and left eyes, and the median stereopsis was within the normal population range. It has been previously shown that stereoacuity does deteriorate in early stages of glaucoma and it is more pronounced with severe disease 40,41. Whether patients maintain their binocular summation ability in moderate or late stage disease remains to be explored in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…It has been previously shown that stereoacuity does deteriorate in early stages of glaucoma and it is more pronounced with severe disease. 40,41 Whether patients maintain their binocular summation ability in moderate or late stage disease remains to be explored in future studies. The integrity of the binocular summation function is expected to be affected in patients with prominent functional and structural asymmetries between the 2 eyes, as occurs in more advanced stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study done to assess the associations between stereoacuity (both near and distance) and the severity of visual field defects (based on HAP and VFI) in POAG, near stereoacuity worsened with POAG severity. However, distance stereoacuity was not associated with POAG severity [ 21 ]. From these, it could be interpreted that impaired depth perception seen in POAG patients is related to the disease process, which could lead to difficulties in activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with glaucoma may suffer from the inconvenience of using anti-glaucoma drugs, economic concerns for the cost of anti-glaucoma treatment, and obstacles faced with the visual impairment of glaucoma. Also, glaucoma impacts individuals in several ways, including a reduced ability to perform self-care activities 4 , decreased steroacuity 5 , being prone to tra c accidents, 6 depression, 7 and falls 8 . Thus, the quality of life (QoL) is strongly in uenced by glaucoma.…”
Section: Introductionmentioning
confidence: 99%